SOC/JS/RER 203: AMERICAN JEWISH LIFE - Tenenbaum, Shelly (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The main objective of this course is to provide students with an introduction to the field ofsociology of American Jewry. Our challenge will be to understand the impact of what, at firstglance, may seem to be contradictory forces: continuity and transformation. On the one hand,American Jewish life is marked by cultural and religious persistence and, on the other hand,characterized by flexibility and change. We will survey a broad range of topics such asimmigration, economic mobility, religious and secular bases of Jewish identity, gender, andintermarriage. In order to identify what is Jewish and what is American about Americans Jews,we will systematically compare Jews with other ethnic groups.